Water filter tank for ecological restoration of mountain water - MA XIAODONG; LI SEN; DONG LIN; GUAN TANGZHEN (2023)
The utility model relates to the technical field of ecological restoration, and provides a water filtering pond for ecological restoration of mountain water, which comprises a pond main body (1) provided with a flow guide inclined plane (2) and a sewage collecting space (5) at the bottom, and a first rotating plate (14) hinged to the side wall of the sewage collecting space (5) and internally connected with a first telescopic plate (15) in a sliding manner, one end of the first telescopic plate (15) is in contact with the bottom of the sewage collection space (5), and one side is hinged to the telescopic end of the first hydraulic cylinder (16); the bottom of the first hydraulic cylinder (16) is fixedly connected to the side wall of the sewage collection space (5); the two supports (20) are connected with a moving block (21) in a sliding mode, the lower end face of the moving block (21) is fixedly connected with an electric telescopic rod (24), the telescopic end of the electric telescopic rod (24) is hinged